Teacher training from the perspective of meaningful learning and active methodologies - Simão de Carvalho, Plauto; Faria Teixeira, Gleicimar; do Couto de Miranda, Sabrina (Aprender, 2023)
Teacher training is seen as an essential practice for the advancement of education. In the face of ongoing sociocultural transformations and changes in the educational landscape, it is essential to provide teachers with resources that encourage them to reframe their teaching practices. In this context, the aim of this study is to contribute to reflection on the relevance of developing continuing teacher training based on meaningful learning and active teaching‐learning methodologies. A theoretical study was carried out using documentary analysis and a bibliographical review of the literature. The arguments presented can encourage the incorporation of the perspective of meaningful learning and active methodologies into training processes, enhancing changes that can reflect positively on the quality of the work carried out in the classroom.
Keywords: teaching; learning; basic education